2000
DOI: 10.1088/0953-2048/13/10/311
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of YBa2Cu3O7-δon Ni89V11non-magnetic biaxially textured substrate using NiO as buffer layer

Abstract: The superconducting YBa2Cu3O7-δ/CeO2/NiO multilayer structure was grown in situ by pulsed-laser deposition on biaxially textured Ni89V11 non-magnetic alloy. The role of vanadium is to decrease the Curie temperature of Ni and to favour the formation of oriented NiO. The (00l)NiO buffer layer has been formed by the controlled oxidation of the Ni-V substrate under 10 mTorr oxygen pressure and at 700 °C. The critical current density of 0.6 MA cm-2, at 77 K and zero magnetic field, was obtained for 0.7 µm thick YBa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The (001)[110] textured NiO layer was obtained in-situ by oxidation of Ni-V substrate at 750°C in 20 mTorr pure oxygen atmosphere for 10 minutes [10]. Ceria films were grown on the Y 2 0 3 /Ni-V structure at 600°C in a 50 mTorr oxygen background pressure.…”
Section: Ybco On Y 2 0 ] 3 -Based Heterostructuresmentioning
confidence: 99%
“…The (001)[110] textured NiO layer was obtained in-situ by oxidation of Ni-V substrate at 750°C in 20 mTorr pure oxygen atmosphere for 10 minutes [10]. Ceria films were grown on the Y 2 0 3 /Ni-V structure at 600°C in a 50 mTorr oxygen background pressure.…”
Section: Ybco On Y 2 0 ] 3 -Based Heterostructuresmentioning
confidence: 99%
“…(1976) reported that it was impossible to produce repeatably a sample with only one or the other of these. A narrow temperature interval in which the (001) oxide orientation is preferentially selected has been reported in studies on textured Ni (Ginsbach et al ., 1991; Matsumoto et al ., 1999, 2000, 2003; Boffa et al ., 2000; Celentano et al ., 2000; Lockman et al ., 2001, 2003; Kursumovic et al ., 2003), but these studies have concentrated on producing cube textured NiO layers for superconducting applications. As a consequence, relatively few results with textured Ni substrates show the oxide microstructure and examine oxide orientations other than the cube texture.…”
Section: Introductionmentioning
confidence: 99%